ANALISIS KEKELIRUAN BAHASA LISAN DAN TULISAN PADA ANAK USIA 6-7 TAHUN BERDASARKAN KONTEKS WACANA - Taqwa, Zayin Zakiya Umma; Fuad, Muhammad; Samhati, Siti; Sumarti, Sumarti; Eko Rusminto, Nurlaksana (Universitas Hamzanwadi, 2024)
Language errors are closely related when someone starts learning a language. Language as a result of speaking has various functions in social life. Children aged 6-7 years are the golden age for children when they will absorb the information and lessons given. Many children aged 6-7 years already receive additional lessons outside of school hours, such as tutoring to enrich their knowledge and train children's language communication. The type of research is descriptive qualitative research, the research was conducted in Labuhan Maringgai, Lampung, the research data is the spoken and written language of children in tutoring courses. The research subjects were 6 year old Andara, 6 year old Gibran and 7 year old Raka. Data was collected by direct observation at the research location emphasizing listening and note-taking techniques. The method of observing and noting is used to analyze language errors spoken by children. The data obtained will be analyzed by reducing the data and drawing conclusions. The analysis is carried out based on the context of the discourse. The results of the research show that the subjects who were children aged 6-7 years old experienced errors in spoken language, that there were still pronunciation errors, foreign words that had just been heard caused pronunciation errors and non-standard words. Written language errors experienced by the subjects included the use of capital letters, errors in the use of hyphens and spelling errors.